Comparison of survey techniques on detection of northern flying squirrels - Corinne A. Diggins; L. Michelle Gilley; Christine A. Kelly; W. Mark Ford (Wildlife Society Bulletin)
ABSTRACT The ability to detect a species is central to the success of monitoring for conservation and management purposes, especially if the species is rare or endangered. Traditional methods, such as live capture, can be labor‐intensive, invasive, and produce low detection rates. Technological advances and new approaches provide opportunities to more effectively survey for species both in terms of accuracy and efficiency than previous methods. We conducted a pilot comparison study of a traditional technique (live‐trapping) and 2 novel noninvasive techniques (camera‐trapping and ultrasonic acoustic surveys) on detection rates of the federally endangered Carolina northern flying squirrel (Glaucomys sabrinus coloratus) in occupied habitat within the Roan Mountain Highlands of North Carolina, USA. In 2015, we established 3 5 × 5 live‐trapping grids (6.5 ha) with 4 camera traps and 4 acoustic detectors systematically embedded in each grid. All 3 techniques were used simultaneously during 2 4‐day survey periods. We compared techniques by assessing probability of detection (POD), latency to detection (LTD; i.e., no. of survey nights until initial detection), and survey effort. Acoustics had the greatest POD (0.37 ± 0.06 SE), followed by camera traps (0.30 ± 0.06) and live traps (0.01 ± 0.005). Acoustics had a lower LTD than camera traps (P = 0.017), where average LTD was 1.5 nights for acoustics and 3.25 nights for camera traps. Total field effort was greatest with live traps (111.9 hr) followed by acoustics (8.4 hr) and camera traps (9.6 hr), although processing and examination for data of noninvasive techniques made overall effort similar among the 3 methods. This pilot study demonstrated that both noninvasive methods were better rapid‐assessment detection techniques for flying squirrels than live traps. However, determining seasonal effects between survey techniques and further development of protocols for both noninvasive techniques is necessary prior to widespread application in the region. Published 2016. This article is a U.S. Government work and is in the public domain in the USA.